Marian Dziamarski (1900–1945) – kapłan, męczennik - Stefańska, Dorota (Biuletyn Szadkowski, 2011)
The article is devoted to Marian Dziamarski, a priest coming from Szadek. His life falls within a period of two world wars and the Polish-Soviet War (1919−1921) – a time which was very important for Polish history and, as many believe, also for the history of Europe. The basis for reflection on the life and activity of M. Dziamarski is his path to the priesthood and the way he fulfilled his vocation. M. Dziamarski participated in the struggle to preserve independence and fought about the shape of the eastern border of the Polish state. After completing education he served as a priest in the eastern territories of Poland. The last years of his life were in the period of occupation − the end of the Second World War brought his tragic death.